Nuclear forensic science in Australia: current status and future plans. (29th July 2019) - Toole, K.; Bull, T.; Keegan, E.; Loi, E.; Goralewski, J.; Lee, S.; Van De Voorde, R.; Young, E.; Ristevska, S.; Roffey, P.; Burger, F.; Cho, K.; et al.
ABSTRACT: The use of nuclear and other radioactive material is expanding globally. An increasing number of countries are signalling their intention to employ nuclear power to meet the energy needs of rapidly growing populations, while socioeconomic development is leading to an increased application of medical and industrial radioisotopes. It is critical that rigorous nuclear security systems are established and maintained to accommodate the increased storage, movement and use of such materials. One aspect of nuclear security is nuclear forensics, which is defined by the International Atomic Energy Agency (IAEA) as 'the scientific analysis of nuclear or other radioactive material, or of other evidence that is contaminated with radionuclides, in the context of international or national law'. In Australia, forensic examination of nuclear or other radioactive material is undertaken by ANSTO, whilst the current capability for the forensic examination of evidence contaminated with radionuclides is jointly held by ANSTO and the Australian Federal Police (AFP). This article describes some of the recent activities undertaken by ANSTO and the AFP to maintain and further develop Australia's nuclear forensic science capability and outline future plans to enhance Australia's capability to provide nuclear forensic support to nuclear security.